2012
DOI: 10.1007/s11999-012-2257-z
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Sexual and Urinary Dysfunction After Surgically Treated Displaced Pelvic Ring Injuries

Abstract: Background Pelvic ring injuries may be associated with genitourinary injury (GUI) and result in urinary or sexual dysfunction. Questions/purposes We determined (1) incidence of new sexual and urinary dysfunction after surgically treated pelvic ring injuries, (2) association of sexual or urinary dysfunction to fracture type and GUI, and (3) incidence and association between new sexual and urinary dysfunction in male and female patients without GUI. Methods We retrospectively studied 151 patients by postal quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Sexual dysfunction after injury to the pelvis has traditionally been attributed to vascular, neurogenic, psychological, and structural damage to the corpora cavernosum and pelvic floor, or a combination thereof. [7][8][9][10][11]30,31 The question of whether we as surgeons have contributed iatrogenic trauma such as suggested in our study does not seem to have been previously asked, let alone answered. To our knowledge, spermatic cord injury associated with clamp application has never been documented, nor has spermatic cord trauma been specifically described associated with pelvic ring injury.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sexual dysfunction after injury to the pelvis has traditionally been attributed to vascular, neurogenic, psychological, and structural damage to the corpora cavernosum and pelvic floor, or a combination thereof. [7][8][9][10][11]30,31 The question of whether we as surgeons have contributed iatrogenic trauma such as suggested in our study does not seem to have been previously asked, let alone answered. To our knowledge, spermatic cord injury associated with clamp application has never been documented, nor has spermatic cord trauma been specifically described associated with pelvic ring injury.…”
Section: Discussionmentioning
confidence: 93%
“…[7][8][9][10][11]30,31 Patients with injuries causing diastasis of the pubic symphysis who underwent symphyseal plating seem to be particularly at risk. For example, Collinge et al 7 showed a 90% rate of erectile dysfunction in men after rotationally unstable "saddlehorn" injuries from horse riding treated with symphyseal plating.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Recent reviews of sexual dysfunction after pelvic fractures by Harvey-Kelly et al and Odutola et al discuss how sexual dysfunction after orthopaedic trauma can considerably decrease patient quality of life. [3][4][5] This was also shown by Borg et al in a 2010 study comparing pelvic fracture patients with favorable outcomes to uninjured patients. Outside the field of orthopaedics, the negative impact of sexual dysfunction on patient quality of life has been well described in urologic, gynecologic, and medical literature.…”
Section: Introductionmentioning
confidence: 52%
“…[1][2][3][4][5][6][7][8][9] It is an important issue to patients, as a survey by the American Association of Hip and Knee Surgeons indicated that up to 89% of patients desire information regarding sexual function after total hip arthroplasty. 1,10 Recent reviews of sexual dysfunction after pelvic fractures by Harvey-Kelly et al and Odutola et al discuss how sexual dysfunction after orthopaedic trauma can considerably decrease patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…3) Studies on the problem related to sexual activity after pelvic ring injury, which is associated with injuries to the neighboring structures can cause sexual problems, 4,5) have been reported often. In the sphere of an acetabular fracture, one study investigated sexual activity which was evaluated as one of the many outcomes following acetabular fractures.…”
Section: Introductionmentioning
confidence: 99%